Hadiths on the Apostate Al-Had and Its Understanding Through the Temporal and Spatial Dimension and Its Application (Raparin Journal of Humanities (RJH), 2024)
The issue of Al-hudud is considered to be one of the important matters. In this respect many texts in Quran and Sunnah have been provided. The good understanding of these texts is urgently needed in order for its understanding to be rectified and how these texts are to be applied. There are a lot of Hadiths (prophet's narrative) about the rule of apostate, but its misinterpretation has led many Muslims to fall into doubts and deviation from the prophetic curriculum due to the fixation on texts and their outward meanings that are understood from the apparent meaning of the text in disregard of other related Hadiths on the same subject. From among those important issues and prerequisite criterions to understand these texts is to take into account the temporal and spatial dimension of those texts. For this end, we must follow the suit of the prophet and his companions who are adopting scientific measurements for the understanding of revered prophetic texts. We have collected all in relation with Ahadith on this matter and we have explained the temporal and spatial impact for the understanding of these Ahadith and their context through many other texts which have been provided on this issue. For this reason, we have chosen this topic and entitled it "Hadiths on the apostate Al-had and its understanding through the temporal and spatial dimension and its application" in an attempt to clarify the effect of temporal and spatial dimension on the understanding and interpretation of the Sunnah of Prophet Mohammed.